Investigating feasible tool for swarm robotic based oil skimming application - Priya R, Padma; Ruchi Sanjay, Agarwal; Vardhan Gupta, Yesho; Rekha, D (International Journal of Engineering and Technology, 2018)
Swarm Robots, a multi-robot system (inspired from insect- groups), work in a decentralized network in a distributed manner [1]. These group of robots coordinate their activities without the need of a universal leader. Instead, they use local rules to track the behavior of the whole group and to communicate information amongst each other. Proper implementation of the swarm robotics system includes executing tasks such as aggregation, assembling, path planning, and pattern formation [2]. Various algorithms may be implemented to realize these tasks and techniques the robots carry out. These algorithms need to be exhaustively tested in terms of robustness, safety and efficiency. Testing of these systems in real-time environments is a matter of great risk to both the resources as well as life. Hence, simulators play a crucial role in the research of swarm robots, more so in applications which require close interaction with the humans [3]. It is equally important to have efficient simulators as it is to have algorithms pertaining to swarm robotics. This study presents a meticulous overview of popular robotic simulation software, some of which could also be used for interfacing in the real robotic environment. A comparison with reference to the oil skimming from oceans using swarm robots as mentioned in the paper is made between the most feasible simulation environments. This is followed by an illustration of the various tasks to be performed by individual robots or group of them.